Colonialism, tourism and place global transformations in tourist destinations - Linehan, Denis (Denis John).; Clark, Ian D. 1958-; Xie, Philip Feifan (Northampton Edward Elgar Publishing, 2020)
"This unique book examines the vital and contested connections between colonialism and tourism, which are as lively and charged today as ever before. Demonstrating how much of the marketing of these destinations represents the constant renewal of colonialism in the tourism business, this book illustrates how actors in the worldwide tourism industry continue to benefit from the colonial roots of globalisation. This interdisciplinary book focuses on the relationships between tourism, colonialism and place, in both historical and contemporary periods. Chapters explore cases of tourism and colonialism in locations across the globe, from colonial Korea and French Indochina, to colonial Australia, U.S Tourism in the British West Indies, heritage tourism in Mozambique, and city branding in Dunedin. Expert contributors analyse the motivations and impacts of colonial tourism, investigating such diverse topics as the Chinese tourist rush to Taiwan, issues of displacement at wildlife sites in Zimbabwe, the impact of tourism on indigenous peoples in Hawaii and the pursuit of Macanese identity and re-colonization. Excavating the range and diversity of colonialism at work in tourism across a wide variety of global destinations, Colonialism, Tourism and Place will be an illuminating read for students and scholars interested in tourism and development, heritage studies, and social, cultural and human geography"-- Provided by publisher.
Keywords: Colonization -- Social aspects; Culture and tourism; Tourism -- Social aspects